PERKECUALIAN TERHADAP PRINSIP LARANGAN PEMBATASAN KUOTA IMPOR TERKAIT PENANAMAN MODAL DI INDONESIA - Raytiaputri, Resa (Jurnal Cakrawala Hukum, 2016)
The existence of an exception from the principle of prohibition on quantitative restrictions related to investments is still not fully reflect justice, especially for developing countries like Indonesia, there is still available a reproach for developed countries or there is multinational companies that have the advantage of capital to take precedence over their interests, but all back at a venture and the power of a country especially developing countries to be able to maintain the sovereignty of his own country from excessive imports.Awareness of the defeat by developing countries regarding technology and capabilities of the product markets of developed countries, made the consistency policies be importance and rules of legislation as one of protection for Indonesia’s national interests amid global competition especially in the field of international trade in capital investment.Considering the capital investment is also needed by Indonesia as one of the efforts to build the national economy and it is very related to international trade.